Analisis Dukungan Keluarga, Ketersediaan Fasilitas Ruang Laktasi Dengan Pemberian ASI Eksklusif Pada Ibu Bekerja - Desi Ekawati (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2022)
Background: Breast milk plays an important role in maintaining the health andsurvival of babies because breast milk is the best food for babies, mothers whohave not exclusively breastfed, one of which is working mothers because thereare many factors that influence breastfeeding for working mothers. This studyaims to analyze the biopsychosocial and institutional factors of exclusivebreastfeedingSubjects and Methods: An observational analytic study with a cross sectionaldesign. The research location is in Bantul district. The research time was in March 2018 with 45 research subjects. Sampling used simple random sampling todetermine the proportion of research subjects. The dependent variable isexclusive breastfeeding. The independent variables are family support, availabilityof lactation room. The data obtained using a questionnaire. Analysis using logisticregression analysis.Results: availability of lactation room (OR=4.15; 95% CI= 1.21 to 14.29;p=0.023), family support (OR=4.82; 95% CI= 1.45 to 15.96; p=0.010), has apositive effect on exclusive breastfeeding .Conclusion: Family support, availability of lactation room, has a positiverelationship with exclusive breastfeeding. Perception of barriers has a negativerelationship with exclusive breastfeedingKeywords: exclusive breastfeeding, health support, working mother